Design and development of a problem-based learning (PBL) e-module in environmental education for enhancing pro-environmental behaviour - Nur Humairoh Umi; Rita Retnowati; Yossa Istiadi (Universitas Pakuan, 2025)
This study aimed to develop an environmental education e-module based on the Problem-Based Learning (PBL) approach to foster pro-environmental behaviour among elementary school students. The research employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, encompassing five sequential stages. The findings indicate that the PBL-based e-module on environmental change effectively enhanced pro-environmental behaviour in Grade V students. Pre-test and post-test analysis yielded an average N-gain score of 0.69 (medium category) and a percentage gain of 68.98% (quite effective category). Furthermore, assessment of pro-environmental behaviour indicators showed high achievement criteria. These results suggest that the developed e-module is both suitable for classroom use and effective in promoting pro-environmental behaviour.